ANALISIS STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN PROFITABILITAS SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Rahmawati, Dewi; Istiono, Istiono (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to determine the influence of capital structure, dividend policy, and profitability on company value. This research was conducted on banking sub-sector companies in the LQ45 category listed on the Indonesia Stock Exchange for the 2018-2023 period. The sample used is a saturated sample where the entire population is sampled. Data collection techniques used company annual report documentation and the data collected was analyzed using multiple linear regression and IBM SPSS Version 25 tools. The research results show that simultaneously capital structure, dividend policy and profitability have a significant effect on company value in banking sub-sector companies in the LQ45 category listed on the Indonesia Stock Exchange for the 2018-2023 period. Meanwhile, partially the capital structure variable has a significant effect on company value. The dividend policy variable does not have a significant effect on company value. The profitability variable has a significant negative effect on company value. The recommendation from this research is that companies need to optimize their capital structure to increase company value and attract investors. Even though dividend policy does not have a significant effect, maintaining a consistent dividend policy is still important to maintain investor confidence. The main focus must remain on increasing profitability because it has a significant influence on company value. It is recommended that further research expand the sample and add other variables such as asset structure, company size, liquidity and solvency in order to obtain more comprehensive and accurate results. Keywords: Capital Structure, Dividend Policy, Profitability, and Firm Value